2021
DOI: 10.3390/genes12081134
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Genomes from Two Specialized Subfamilies of Reduviidae (Insecta: Hemiptera) Reveal Novel Gene Rearrangements of True Bugs

Abstract: Reduviidae, a hyper-diverse family, comprise 25 subfamilies with nearly 7000 species and include many natural enemies of crop pests and vectors of human disease. To date, 75 mitochondrial genomes (mitogenomes) of assassin bugs from only 11 subfamilies have been reported. The limited sampling of mitogenome at higher categories hinders a deep understanding of mitogenome evolution and reduviid phylogeny. In this study, the first mitogenomes of Holoptilinae (Ptilocnemus lemur) and Emesinae (Ischnobaenella hainana)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The atp8 gene had the highest Ka / Ks value, consistent with the previously identified Ka / Ks ratios in spider species ( Kumar et al, 2020 ; Li et al, 2021 ), and insects ( Chakraborty et al, 2018 ; Li et al, 2019 ; Chang et al, 2020 ; Ye et al, 2021 ). It has been reported that different mitochondrial PCGs evolved at different rates ( Li et al, 2012 ; Zapelloni et al, 2021 ), as has been found in RTA species.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The atp8 gene had the highest Ka / Ks value, consistent with the previously identified Ka / Ks ratios in spider species ( Kumar et al, 2020 ; Li et al, 2021 ), and insects ( Chakraborty et al, 2018 ; Li et al, 2019 ; Chang et al, 2020 ; Ye et al, 2021 ). It has been reported that different mitochondrial PCGs evolved at different rates ( Li et al, 2012 ; Zapelloni et al, 2021 ), as has been found in RTA species.…”
Section: Discussionsupporting
confidence: 89%
“…These ten RTA mitogenomes were biased toward A and T, consistent with previous findings ( Zhu et al, 2019 ; Li et al, 2020 ). Arthropod mitogenomes tend to have a positive AT-skew and a negative GC-skew on the J-strand, i.e., most species showed the strand asymmetry ( Wang et al, 2017 ; Ye et al, 2021 ). However, the strength of the skews in the mitogenomes of the RTA clade showed the opposite pattern, indicating that the J-strands of these mitogenomes have strand asymmetry reversal and favored T and G. This seemed to be a common phenomenon in Araneae ( Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene arrangement of almost all insect mitogenomes is compact according to the ancestral phenotype, but exceptions have been detected in some orders, including Hymenoptera, Hemiptera, Ephemeroptera, and Mantodea, among others [ 28 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Gene rearrangements are a relatively common phenomenon in insects, but gene duplications are rare [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite gene content being preserved in most metazoans, gene arrangements and duplications can distinguish specific evolutionary lineages [ 6 ]. As gene rearrangements are generally uncommon within but vary among major lineages, their study allows for the resolution of taxonomic relationships using mitochondrial genome analysis (mitogenomics), unravelling complex evolutionary histories [ 6 , 8 ]. Fragments of the mitogenomes can also be transferred into the nuclear DNA, constituting nuclear mitochondrial DNA sequences (NUMTs).…”
Section: Introductionmentioning
confidence: 99%